Pengaruh Perilaku Ibu Selama Kehamilan terhadap Status Kehamilan yang Tidak Diinginkan di Indonesia - Guspaneza, Essi; Martha, Evi (Media Kesehatan Masyarakat Indonesia, 2019)
Unwanted pregnancy status occurs because the mother have not ready to get pregnant and will the impact on maternal behavior during pregnancy made mother tend to less doing the antenatal care visits, or prenatal care visits. This study aims to know the effect of maternal behavior during pregnancy towards unwanted pregnancy status. This study is a quantitative with using cross-sectional study design. The population is all pregnant women from 2017 IDHS survey in Indonesia of 1990 women, analyzed with univariate, bivariate and multivariate. The results of the research showed women who having unwanted pregnancy of 12.8% and there are relationship between maternal behavior during pregnancy (p=0.0001;OR=39,640) with unwanted pregnancy, after controlled age at pregnancy and parity. The probability of mothers who not doing ANC visit, parity >3 and age at pregnancy <20 or >35 years having unwanted pregnancy status by 55%. Conclusion of this study is that there are effect maternal behavior during pregnancy (ANC visits) towards unwanted pregnancy status.